Reducing Same Day Cancellations Due to Patient Related Factors in Elective Orthopaedic Surgery: Experience of a Centre in the Uk. Issue 4 (April 2014) - Singhal, R; Warburton, T; Charalambous, Cp
Cancellations on the day of surgery represent a major wastage of resources and can impose significant distress on patients. Minimising same day cancellations can improve cost effectiveness of operating theatre running. The aim of the study was to determine the impact of administering a questionnaire, by phone to elective orthopaedic patients, the week prior to surgery. This questionnaire was aimed at identifying factors that could lead to same day cancellation for patient related reasons. The questionnaire was administered to elective orthopaedic patients over a nine month period. The rate of same day cancellations due to patient related reasons in this cohort (Phase 2) was compared with a previous cohort assessed over a five month period when the questionnaire was not in place (Phase 1). Administering the questionnaire reduced the same day cancellations due to patient reasons from 11 out of 110 (10%) to 2 out of 118 (1.60%) (p = 0.01). Theatre wastage in terms of national tariff lost due to cancellations was reduced from £25, 881 to £1, 650 (p<0.001). The study concludes that administering a questionnaire aimed at addressing patient related reasons can significantly reduce same day cancellations.